Mapping the Potentials and Challenges of Emerging Tourism Villages: Reflections from the ASTACITA Forum as a Strategic Planning Foundation - Samerdanta Sinulingga; Meutia Nauly; Jonathan Liviera Marpaung (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This article presents an early-stage analysis of the potentials and challenges faced by emerging tourism villages, using the ASTACITA Summit 2025 as a case study. Held in Kuta Gugung Village, North Sumatra, ASTACITA (Strategic Alliance for Collaborative, Inclusive, and Integrated Village Governance) served as a pioneering forum for multi-stakeholder engagement in rural development. The forum brought together actors from government, academia, business, community, and media within a structured dialogue aimed at empowering rural communities through participatory tourism planning. Utilizing a qualitative descriptive method, data were collected through participant observation, informal interviews, and documentation of collaborative sessions during the summit. The study mapped key village potentials including cultural uniqueness, natural attractions, and local entrepreneurial initiatives as well as pressing challenges such as infrastructural limitations, governance gaps, and lack of digital capacity. Through structured discussion tables and networking exchanges, the forum enabled a bottom-up identification of strategic priorities, including training needs, partnership opportunities, and local regulation frameworks. Findings suggest that the ASTACITA format not only facilitated knowledge transfer but also generated community-driven insights that can inform long-term development planning. The mapping process served as a reflective and inclusive diagnostic tool that centered local voices while aligning with national rural tourism goals. This study contributes to the discourse on participatory governance and sustainable tourism by showcasing how structured forums like ASTACITA can be harnessed for strategic, data-informed, and collaborative planning in rural contexts.